Optical control and detection of spin coherence in multilayer systems. - Ullah, Saeed (2017)
Since a decade, spintronics and related physics have attracted considerable attention due to the massive research conducted in these areas. The main reason for growing interest in these fields is the expectation to use the electrons spin instead of or in addition to the charge for the applications in spin-based electronics, quantum information, and quantum computation. A prime concern for these spins to be possible candidates for carrying information is the ability to coherently control them on the time scales much faster than the decoherence times. This thesis reports on the spin dynamics in two-dimensional electron gases hosted in artificially grown III-V semiconductor quantum wells. Here we present a series of experiments utilizing the techniques to optically control the spin polarization triggered by either optical or electrical methods i.e. well known pump-probe technique and current-induced spin polarization. We investigated the spin coherence in high mobility dense two-dimensional electron gas confined in GaAs/AlGaAs double and triple quantum wells, and, it\'s dephasing on the experimental parameters like applied magnetic field, optical power, pump-probe delay and excitation wavelength. We have also studied the large spin relaxation anisotropy and the influence of sample temperature on the long-lived spin coherence in triple quantum well structure. The anisotropy was studied as a function sample temperature, pump-probe delay time, and excitation power, where, the coherent spin dynamics was measured in a broad range of temperature from 5 K up to 250 K using time-resolved Kerr rotation and resonant spin amplification. Additionally, the influence of Al concentration on the spin dynamics of AlGaAs/AlAs QWs was studied. Where, the composition engineering in the studied structures allows tuning of the spin dephasing time and electron g-factor. Finally, we studied the macroscopic transverse drift of long current-induced spin coherence using non-local Kerr rotation measurements, based on the optical resonant amplification of the electrically-induced polarization. Significant spatial variation of the electron g-factor and the coherence times in the nanosecond scale transported away half-millimeter distances in a direction transverse to the applied electric field was observed.